Methodologies of teaching and training in higher educational institutions of the EU and Ukraine - ZHURAVSKA, Nina (Journal of Education, Technology and Computer Science, 2014)
Why you need a teacher in high school, just as the carrier and transmitter ofinformation? But it is in this capacity he is much inferior to many other sourcesof information such as books and computers. Higher education institution servesnot only and may be not so much for the transfer specialized knowledge but forthe development and reproduction of specific cultural group, the most importantelement of which is itself a specialist. He is characterized as a representative ofa particular culture not only a specific set of knowledge and skills, but alsoa certain worldview, life attitudes and values, especially the of professional conductand others. So the teacher not only sends the student knowledge and professionalskills, and attaches it to a specific culture, and that this culture was developedand reproduced needed live people, live human communication. This truthmore than a hundred years ago formulated by K. D. Ushinsky: “Only a personcan act on the development and definition of personality, only nature can beused to form the character” [Ушинский 1984: 78–83].